Pengembangan kurikulum inti program studi PKn: perspektif PKn sebagai disiplin ilmu dan PKn persekolahan - Cholisin Cholisin (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
The draft of core curriculum (national curriculum) if undergraduate program if civic education (S1) is developed upon the agreement between civic education departments from several higher education institutions /faculties of teacher training and education accepted partnership block grant for developing the core curriculum This draft is hoped to be accepted as standard both for those in agreement and not. The core curriculum is developed from the essences of field of study, namely social, professional, personal, and pedagogic competences. From these essences of field study, learning experiences; facilities, education; and academic qualification of lecturer are developed: It was agreed that 60% of the total credits is developed from these essences of field study and the rest (40%) is delegated to each institution in developing